A study of energy dissipating mechanisms in orthogonal cutting of UD-CFRP composites. (15th July 2019) - Yan, Xiaoye; Reiner, Johannes; Bacca, Mattia; Altintas, Yusuf; Vaziri, Reza
Abstract: This paper presents a three-dimensional thermo-mechanical finite element (FE) model on the micro-scale for the orthogonal cutting simulation of unidirectional carbon fiber reinforced polymer (UD-CFRP) materials. Fiber, matrix and the fiber-matrix interface are modeled separately to simulate failure mechanisms associated with fiber breakage, matrix cracking and fiber-matrix debonding. Experiments on orthogonal cutting of UD-CFRP workpieces with various fiber orientations have been conducted and compared to the micro-scale FE simulations. The good correlation between the experimental and numerical results with respect to cutting forces, chip formation and surface quality enables for an in-depth FE energy analysis to quantify dominating failure mechanisms in different fiber orientations. In addition, the contribution of each fiber failure mode during orthogonal cutting is evaluated. It is found that dissipated energies associated with various failure modes and friction vary with the fiber orientations and that the simulation provides insight into the characteristic fiber orientation-dependent quantities observed in the experiments such as chip formation and surface morphology. Finally, a sensitivity analysis is carried out to assess the variation of the simulated cutting response with respect to input parameters with high uncertainty including friction coefficients or fiber strength values.